The Effect of Problem Based Learning Model on Front Kick Mastery in Pencak Silat Learning at SMA Negeri 2 Karawang - Kiki Hidayattullah; Rahmat Iqbal; Astri Ayu Irawan (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study, among others, is to determine the effect of the problem based learning on the mastery of the front kick movement in learning pencak silat at SMA Negeri 2 Karawang. This study uses an experimental quantitative approach. This study was made using a pre-experimental form of a one group pretest-posttest design. The place of this research is in SMA Negeri 2 Karawang. This research was conducted in July – August 2022 with 8 meetings. The population in this study was class XI students at SMA Negeri 2 Karawang. Sampling using the technique of "purposive sampling". The author took samples based on certain criteria so that the sample in this study amounted to 33 people. This research instrument uses a test instrument to collect research data. based on the results of the calculation data that has been carried out, it is obtained that the pretest has an average calculation result of 27.27 and the posttest with an average of 36.06 indicate that the pretest has a smaller calculation result than the resultscalculation posttest. The data analysis technique in this study uses statistical , including: normality test, it is known that the statistical test value in the pretest is 0.933 and the posttest 0.941. The homogeneity test of the pretest-posttest obtained a significance value of 0.567 because the sig value of 0.567> of 0.05. The t-test table paired sample test output are known to have the Sig value. (two tilled) of 0.000 < 0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is a difference between pretest and posttest and means that there is an effect of the problem based learning on the mastery of front kicks in learning pencak silat at SMA Negeri 2 Karawang.